2020
DOI: 10.1007/s00208-020-01964-z
|View full text |Cite
|
Sign up to set email alerts
|

Gravitating vortices and the Einstein–Bogomol’nyi equations

Abstract: In this work we consider the gravitating vortex equations. These equations couple a metric over a compact Riemann surface with a hermitian metric over a holomorphic line bundle equipped with a fixed global section -the Higgs field -, and have a symplectic interpretation as moment-map equations. As a particular case of the gravitating vortex equations on P 1 , we find the Einstein-Bogomol'nyi equations, previously studied in the theory of cosmic strings in physics. We prove two main results in this paper. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…As can be seen in other similar problems (see e.g. [14], [16], [21], [1]), the two obstructions of the Lie algebra character and the reductiveness come always in pair. The purpose of this paper is to show that this is the case, namely the following is the main result of this paper.…”
Section: Introductionsupporting
confidence: 52%
“…As can be seen in other similar problems (see e.g. [14], [16], [21], [1]), the two obstructions of the Lie algebra character and the reductiveness come always in pair. The purpose of this paper is to show that this is the case, namely the following is the main result of this paper.…”
Section: Introductionsupporting
confidence: 52%
“…Nonetheless, as the recent result of Han-Sohn [15] showed, Yang's existence result does not exhaust all the possible solutions (see a detailed discussion in Section 2.2). For c 0, the first two authors jointly with Álvarez-Cónsul and García-Prada found a new obstruction to the existence of solutions of (2.2), thus establishing a relation with Geometric Invariant Theory (GIT) for these equations [2,4]. For c < 0, the existence and uniqueness of solutions has been established in [4] in genus greater than one for a suitable range of the coupling constant α, depending only on the topology of the surface and the line bundle.…”
Section: Introductionmentioning
confidence: 97%
“…For c 0, the first two authors jointly with Álvarez-Cónsul and García-Prada found a new obstruction to the existence of solutions of (2.2), thus establishing a relation with Geometric Invariant Theory (GIT) for these equations [2,4]. For c < 0, the existence and uniqueness of solutions has been established in [4] in genus greater than one for a suitable range of the coupling constant α, depending only on the topology of the surface and the line bundle. For c > 0, the analytical techniques in [4,15,29] do not apply, and the existence problem has hitherto remained open.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations